2005
DOI: 10.1159/000088702
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo among Elderly Patients in Primary Health Care

Abstract: Background:Dizziness influences well-being in old age, and benign paroxysmal positional vertigo (BPPV) is a common cause. The condition is diagnosed using the Hallpike maneuver and treated by the particle-repositioning maneuver or habituation exercises. Objective:To identify patients with BPPV among a variety of diagnoses represented by the ICD-10 diagnosis R42 in people 65 aged years and older who visited primary health care because of vertigo and dizziness. Methods:Searches were performed in the computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…The fact that 29% of our dizzy patients were not assigned a specific diagnosis is in accordance with other descriptions of a relatively high frequency of "unspecific dizziness" in primary care [28] or with understanding dizziness as a geriatric syndrome [4]. Our study confirmed BPPV as a relatively common [8], but frequently underestimated cause of dizziness among older people in primary care [29], although it can be easily assessed and effectively treated [30]. …”
Section: Discussionsupporting
confidence: 88%
“…The fact that 29% of our dizzy patients were not assigned a specific diagnosis is in accordance with other descriptions of a relatively high frequency of "unspecific dizziness" in primary care [28] or with understanding dizziness as a geriatric syndrome [4]. Our study confirmed BPPV as a relatively common [8], but frequently underestimated cause of dizziness among older people in primary care [29], although it can be easily assessed and effectively treated [30]. …”
Section: Discussionsupporting
confidence: 88%
“…Underdiagnoses might also be frequent, given the high rate of symptom-only diagnoses. This might be particularly so for certain vestibular disorders, such as multisensory disequilibrium (common among older patients 37 but not available as a specific ICD-9-CM diagnosis code) or vestibular migraine (common at any age but probably unrecognized by many physicians 38 ). Finally, perhaps some diagnoses were incidental to the symptom of dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that BPPV is common, it has a low recognition rate in primary care, especially in older adults . It is likely that failure to diagnose BPPV correctly accounts for the high proportion of individuals who receive inappropriate diagnostics and the low proportion who receive appropriate symptom relief.…”
Section: Diagnostic Approachmentioning
confidence: 99%